2013
DOI: 10.1155/2013/480476
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Pseudotumor of the Temporal Bone: Three Cases and a Review of the Literature

Abstract: Inflammatory pseudotumor (IP) is a clinically aggressive but histologically benign condition of unknown cause. Its appearance in the temporal bone is uncommon. We present clinical, radiological, and histopathologic findings of three cases originating in the temporal bone. In the first case, a simultaneous IP of the temporal bone and parotid gland was found with histopathologic confirmation. In the second case, an enlarged cervical node, which was also believed to be related to IP, was observed accompanied with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…(See Table 3). One review in 2013 identified only 29 cases 6 . We are only able to speculate as to why our institution has had a high population of patients with the diagnosis of IPT over the past several years despite no objective data to support a long-term, significant increase in diagnosis of IPT within the head and neck or other areas of the body.…”
Section: Discussionmentioning
confidence: 99%
“…(See Table 3). One review in 2013 identified only 29 cases 6 . We are only able to speculate as to why our institution has had a high population of patients with the diagnosis of IPT over the past several years despite no objective data to support a long-term, significant increase in diagnosis of IPT within the head and neck or other areas of the body.…”
Section: Discussionmentioning
confidence: 99%
“…To date, less than 50 cases of IPT involving the temporal bone have been reported (Table 1). 2,5‐32 Therefore, the clinical physiology of IPT in the temporal bone has not been fully understood, and no standard treatment has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Past treatments have included combinations of steroids, surgical resection, radiation, and/or immunomodulators. Treatment with immunomodulators have included cyclophosphamide, mycophenolate mofetil, methotrexate, alpha interferon, azathioprine, and rituximab (1,2,4,(8)(9)(10)(11)(12)(13). Complete resection is preferred; however, tumor location may prevent a safe and tolerable approach (2).…”
Section: Introductionmentioning
confidence: 99%